Impulse-Control Disorders in a College Sample: Results From the Self-Administered Minnesota Impulse Disorders Interview (MIDI) - Odlaug, Brian L. (Physicians Postgraduate Press, Inc., 2010)
OBJECTIVE: This study sought to examine the prevalence rates of and gender differences among impulse-control disorders in a college sample. METHOD: During the fall semester of 2006, 791 college students from 2 private colleges in the Midwest completed a self-administered, modified version of the Minnesota Impulse Disorders Interview to assess lifetime rates of DSM-IV-TR–diagnosed impulse-control disorders. Participation was voluntary and anonymous. RESULTS: The mean age of the sample was 20.0 ± 1.25 years, with females comprising 67.9% of the respondents. Of the individuals, 10.4% (n = 82) met criteria for at least 1 lifetime impulse-control disorder. The most common disorders were trichotillomania (3.91%) and compulsive sexual behavior (3.66%). Kleptomania was the least common (0.38%). Males were significantly more likely to screen positive for pathological gambling (P = .003) and compulsive sexual behavior (P = .002). Females were more likely to have compulsive buying (P = .033). CONCLUSIONS: Impulse-control disorders appear to be common among college students. The high rates indicate that these disorders may be incipient during late adolescence and early adulthood and should be addressed prior to onset of clinical versions of the impulse-control disorder.